An Essay on Man - Pope, Alexander, 1688-1744 (Book collections on Project MUSE., 2016)
Voltaire called it "the most sublime didactic poem ever written in any language." Rousseau rhapsodized about its intellectual consolations. Kant recited long passages of it from memory during his lectures. And Adam Smith and David Hume drew inspiration from it in their writings. This was Alexander Pope's Essay on Man (1733-34), a masterpiece of philosophical poetry, one of the most important and controversial works of the Enlightenment, and one of the most widely read, imitated, and discussed poems of eighteenth-century Europe and America. This volume, which presents the first major new edition of the poem in more than fifty years, introduces this essential work to a new generation of readers, recapturing the excitement and illuminating the debates it provoked from the moment of its publication. Echoing Milton's purpose in Paradise Lost, Pope says his aim in An Essay on Man is to "vindicate the ways of God to man"--To explain the existence of evil and explore man's place in the universe. In a comprehensive introduction, Tom Jones describes the poem as an investigation of the fundamental question of how people should behave in a world they experience as chaotic, but which they suspect to be orderly from some higher point of view. The introduction provides a thorough discussion of the poem's attitudes, themes, composition, context, and reception, and reassesses the work's place in history. Extensive annotations to the text explain references and allusions. The result is the most accessible, informative, and reader-friendly edition of the poem in decades and an invaluable book for students and scholars of eighteenth-century literature and thought.